Evolutionary Perspectives on the Developing Skeleton and Implications for Lifelong Health - Kralick, Alexandra E.; Zemel, Babette S. (Frontiers in Endocrinology, 2020)
Osteoporosis is a significant cause of morbidity and mortality in contemporary populations. This common disease of aging results from a state of bone fragility that occurs with low bone mass and loss of bone quality. Osteoporosis is thought to have origins in childhood. During growth and development, there are rapid gains in bone dimensions, mass, and strength. Peak bone mass is attained in young adulthood, well after the cessation of linear growth, and is a major determinant of osteoporosis later in life. Here we discuss the evolutionary implications of osteoporosis as a disease with developmental origins that is shaped by the interaction among genes, behavior, health status and the environment during the attainment of peak bone mass. Studies of contemporary populations show that growth, body composition, sexual maturation, physical activity, nutritional status and dietary intake are determinants of childhood bone accretion, and provide context for interpreting bone strength and osteoporosis in skeletal populations. Studies of skeletal populations demonstrate the role of subsistence strategies, social context, and occupation in the development of skeletal strength. Comparisons of contemporary living populations and archeological skeletal populations suggest declines in bone density and strength that have been occurring since the Pleistocene. Aspects of western lifestyles carry implications for optimal peak bone mass attainment and lifelong skeletal health, from increased longevity to circumstances during development such as obesity and sedentism. In light of these considerations, osteoporosis is a disease of contemporary human evolution and evolutionary perspectives provide a key lens for interpreting the changing global patterns of osteoporosis in human health.